CEACAM6 serves as a biomarker for leptomeningeal metastasis in lung adenocarcinoma. (9th September 2022) - Wang, Xueying; Tang, Xuemei; Gu, Jiahui; Sun, Ziwei; Yang, Shengrui; Mu, Yuan; Guan, Ming; Chen, Kun; Liu, Wei; Ruan, Haoyu; Xu, Jian
Abstract: Background and aims: Diagnosis of leptomeningeal metastasis (LM) is challenging. In our previous study, CEACAM6 mRNA was found to be highly expressed in the circulating tumor cells of cerebrospinal fluid (CSF) from patients with lung adenocarcinoma with LM (LUAD‐LM). The aim of this study was to identify whether CEACAM6 could be used as a biomarker for LUAD‐LM. Materials and methods: The level of CEACAM6 was determined by enzyme‐linked immunosorbent assay (ELISA) in CSF from 40 LUAD‐LM and 44 normal controls, and additional serum samples from 138 LUAD patients, including 12 LUAD‐LM patients, and 30 healthy controls. Carcinoembryonic antigen (CEA), cytokeratin 19 fragment (CYFRA 21‐1) and neuron‐specific enolase (NSE) levels in the CSF and sera were detected by chemiluminescent immunoassay. Receiver operating characteristic curve was plotted to evaluate the diagnostic performance for LUAD‐LM. Results: CSF CEACAM6 level was higher in LUAD‐LM than that in normal controls. In serum, LUAD patients had a higher level of CAECAM6 than healthy controls, and LM patients had the highest level among them. Serum CEACAM6 had a higher AUC than CEA in differentiating LM from non‐LM in LUAD patients (0.95 vs. 0.64, p < 0.001). Conclusion: CEACAM6 may serve as a potential biomarker in diagnosing LUAD‐LM. Abstract : CEACAM6 in the CSF was higher in LUAD‐LM than benign diseases. LUAD‐LM patients had a higher level of serum CAECAM6 than healthy controls and non‐LM LUAD patients. Serum CEACAM6 had a higher AUC than CEA in differentiating LM from non‐LM in LUAD. CEACAM6 may serve as a potential biomarker in diagnosing LUAD‐LM.